SAFETY OF COMBINED INJECTION OF VACCINES AGAINST HIB-INFECTION (the data on pilot project fulfilled in Murmansk region and Yaroslavl) - S.M. Kharit; V.Yu. Rodnikova; T.A. Druzhinina; E.Ya. Frolova; O.K. Mamontova ("Paediatrician" Publishers LLC, 2009)
The results of an observation of 288 children under the age 3-20 months old (46 healthy infants and 142 patients with allergic diseases, residual lesions of CNS, frequently ailing ones and infants with other pathologies), vaccinated and re-vaccinated with Hiberix and Infanrix in one syringe were analyzed. High safety of such method of injection allowed decreasing of injection load during the vaccination against hemophilic infection type b in infants. Common moderate reaction was detected in only one child (0,5%). Topical reactions were registered in 5,0% of vaccinated patients.Key words: children, hemophilic infection, vaccination, post-vaccinal period, safety.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):36-41)